SMARTPHONE RECOMMENDATION DECISION SUPPORT SYSTEM USING THE TOPSIS METHOD - Dani Sifa Abdillah; muhamad Fuat Asnawi (Nacreva Publisher, 2024)
Many smartphone brands with various specifications and competitive prices often make consumers confused when deciding which smartphone to buy. There are many choice factors for consumers to buy the right smartphone according to their use, while the choice of smartphone is still considered subjective, so it is not uncommon for the choice of smartphone to be less than optimal. The aim of this research is to recommend the best smartphone based on predetermined usability and price criteria, including gaming needs, content creators and low price using the Technique for Others Preference by Similarity to Ideal Selection (TOPSIS) method. The results of the process of implementing the TOPSIS method can display alternative ranking data from the largest value to the smallest value.